Human skin permeation rates ex vivo following exposures to mixtures of glycol ethers. (15th December 2020) - Berthet, Aurélie; Oltramare, Christelle; Spring, Philipp; Hechon, Julie; Hopf, Nancy B.
Highlights: PGBE, as PGME, permeates rapidly (<2 h, 22 μg/cm 2 /h) through fresh skin. Skin permeation coefficients for PGME and PGBE were altered when applied together. Skin permeation for PGME and PGBE mixtures were also altered for frozen skin. Skin permeation rates were greater for previously frozen compared to fresh skin. Abstract: Skin exposure to cleaning products in the general and occupational population are a public health concern. Among the most frequently identified amphiphilic organic solvents in cleaning products are propylene glycol monomethyl ether (PGME) and propylene glycol n-butyl ether (PGBE). Internal dose from skin exposure may be efficiently evaluated using in vitro flow-through diffusion cells with excised human skin. Our aim in this study was two-fold; 1) characterize the permeation rates (J), time lag (Tlag ), and permeation coefficients (Kp) of PGME and PGBE in human ex-vivo skin permeation assays, and 2) determine a possible mixture effect on skin permeation characteristics when applied together. Our results showed a short Tlag for PGME and was reduced further depending on the amount of PGBE in the mixture (Tlag was reduced from 2 h to 1–1.7 h) for fresh skin. PGBE Tlag slightly increased when mixed with 50 % or more PGME. Permeation rate decreased to half for both PGME and PGBE in mixture at any concentration. This substantial permeation was greater with previously frozen skin. This mixture effect could favor permeation of other compounds through human skin.